Capacitance creep and recovery behavior of magnetorheological elastomers. (August 2021) - Fan, Yuqin; Qin, Hong; Lu, Chuan; Liao, Changrong; Chen, Xianping; Yu, Jiabing; Xie, Lei
As a novel conductive elastomer, magnetorheological elastomers (MREs) featuring both high sensitivity and wide working range have been employed as a new sensing material for flexible tactile sensors. Their sensing mechanism, that is, the spatial distribution rearrangement of particles under compression, completely differs from their conventional counterparts. The piezo-capacitive effect of MREs resulting from the unique mechanism of particles rearrangement is actually a response to the microscopic mechanical movement of particles. This nature brings a core concern on the intrinsic relationship between their mechanical and electrical properties. This study illuminates them from the perspective of electrical creep and recovery behavior of MREs. We give a meaningful analysis for the capacitance creep-recovery mechanism. The experimental fact strongly demonstrated that the particles rearrangement was the direct cause, while the strain creep was an indirect cause. All the behaviors were well interpreted by an evolution mechanism of the particles rearrangement driven by the mechanical strain creep of the flexible matrix under constant pressure. In simpler terms, the electrical creep was induced by the mechanical creep. We further explored the creep effect in practical applications and found a "self-healing" behavior, which indicated that the MRE sensors could obtain a stable sensing capability after a pre-processing.